Nancy Rose Hunt, A Nervous State: Violence, Remedies, and Reverie in Colonial Congo (Historia, 2021)
A Nervous State: Violence, Remedies, and Reverie in Colonial Congo provides a fascinating re-reading of the history of the Congo in general and medical history in Central Africa in particular. Specifically, the book examines the everyday experiences of the Congolese on the one hand and the colonial officials, priests, nuns, medical doctors, etc. on the other, between 1885 and 1960. In all this, violence was central to the system that sustained the Congo Free State and its successor the Congo State. Scholars have demonstrated the long history of violence deployed on the Congolese by the colonisers. The gruesome accounts of colonial brutality – cutting off of human hands, rape and war – have led to the story of Congo being associated with searing violence and horror. Without denying or underplaying the significance of violence in sustaining the colonial subjugation of the Congolese, Nancy Rose Hunt shifts the angle of analysis by focusing on the narratives that place emphasis on the history of a nervous colonial state.
Keywords: Colonial Congo; Congo Free State; Leopold; Maria Nkoi; Congo; Nervous State